Penguatan karakter Pemuda Desa Sambelia Malalui Gawa Adat “ Selametan Otak Reban” - Junaidi Junaidi; Faizi Anwar; Nada Salwa; Siti Zulfiana; Mashal Hadi (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The purpose of this community service activity is to strengthen the character of the young men and women of Sambelia village through the traditional gawe "Selametan Otak Reban". The method used in this study is direct practice by participating in the traditional gawe activities "Selametan Otak Reban" Sambelia Village. This community service process was carried out at the Otak Reban traditional hall of Sambelia Village, which was attended by all levels of the Sambelia Village community, which was attended by the Deputy Regent H. Edwin and Mrs. Marianah as DPRD Davil V. This traditional event aims to (1) Preserve culture (2) Honor ancestors, (3) Express gratitude, (4) Inherit cultural values, (5) Strengthen social ties. The results of this research are expected to be able to create the next generation of young men and women from Sambelia Village. It is hoped that the young men and women from Sambelia Village will be able to strengthen ties of friendship, strengthen character, have an understanding of the village's cultural heritage, love and cultivate the traditional event "Selametan Otak Reban".